PEMANFAATAN CITRA SATELIT RESOLUSI SANGAT TINGGI (CSRST) UNTUK PENYUSUNAN PETA DASAR RENCANA DETAIL TATA RUANG KECAMATAN GROGOL KABUPATEN SUKOHARJO - Rio Andrianto; Yunus Aris Wibowo; Yudhistira Tri Nurteisa (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2026)
UTILIZATION OF VERY HIGH RESOLUTION SATELLITE IMAGERY (CSRST) FOR PREPARATION OF BASE MAP FOR DETAILED SPATIAL PLANNING OF GROGOL DISTRICT, SUKOHARJO REGENCY Maps can be drawn on a flat surface with a certain scale, numbering, projection, and georeference so that they can be a reference for making various thematic maps needed in compiling regional planning documents such as RTDR. This study aims to analyze the use of Pleiades very high resolution satellite imagery (CSRST) with a spatial resolution of 2 meters (Multispectral/MS) and 0.5 meters (Panchromatic/PAN) for compiling the base map of the RDTR of Grogol District, Sukoharjo Regency. The creation of this base map uses data in the form of Geospatial Data (DG) which is then further processed to produce Geospatial Information (IG) as stated in Law Number 4 of 2011. The methods used in this study include the stages of initial identification, literature study, horizontal accuracy test, digitization of base map elements, topology and attribute filling, preparation of tentative maps and field surveys, data cleaning, attribute editing, and database formation, and preparation of the RDTR map. The results of data analysis and processing, produce land cover data covering 6 elements in the form of buildings and public facilities totaling 58,639 units, waters totaling 336 types, transportation with a length of 435.79 km, open areas of 1197,717 hectares, agriculture and livestock 849,0354 hectares, and the number of toponyms totaling 1417 points. The layouting process refers to cartographic principles and aesthetic elements of the map, for layouting there are RDTR map layouts and NLP layouts where in the Grogol area it consists of 7 NLPs.